AN EFFECTIVE RELIGIOUS MODERATION EDUCATION MODEL FOR A DIVERSE STUDENT - Sismanto, Sismanto (Proceeding of International Conference on Islamic Education (ICIED); Vol 6 No 1 (2021): Proceeding of International Conference on Islamic Education (ICEID), 2021)
This article aims to analyze and discusses an effective religious moderation education of multicultural education issues, religious moderation education model, and finding new solutions for diverse students by using a qualitative approach with multi-site in private and public school East Kalimantan. The author collects data through interviews and FGDs and explores reputable journals and several relevant references. The findings reveal that: (1) Schools to be used as places to teach religious moderation to diverse students and its implementation strategy through curriculum integration in each lesson, extracurricular activities, and habituation in school and daily home environment. (2) The religious moderation education model are formulated in the school's vision. (3) Effective religious moderation education for diverse students includes well-designed teacher development programs and strong school and home relationships.